(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The nomination of domestic ceremonies in the manners of speaking of podil’sko-bukovinsko-naddnistryanskogo boundary is devoted in the article. The work is based on the materials independently collected on the special program considerable on a volume empiric material – facilities of nomination, which presentation of domestic ceremonies is presented in the manners of speaking of podil’sko-bukovinsko-nadnistryanskogo boundary. The expressive contrasting of the naddnistryan’skogo, bukovyns’kogo and podil’skogo dialects is confirmed and value of the rivers which carried out the role of administrative limits in the past, as lines of the interdialectal differentiating.